Lanostanoid triterpenes from the fungus Rigidoporus microporus. Issue 21 (2nd November 2021) - Rincón, Yuliet A.; Siless, Gastón E.; Amado, Lucía Daniela; Dansey, María Virginia; Grassi, Emanuel; Schenone, Nahuel; Cabrera, Gabriela M.
Abstract: Five new lanostanoid triterpenes were isolated from the extract of R. microporus . Three of the metabolites (1–3 ) present a Δ 8, 9 skeleton with an uncommon keto functionality at C–1. Another compound (4 ) has an unprecedented rearranged skeleton in which methyl-19 was transposed to C–1, with conjugated double bonds at Δ 1–10 and Δ 8–9 . All of the compounds have hydroxylated or furane-cyclized side-chains. The structures were elucidated by spectroscopic methods, and the absolute configuration of the hydroxyl-bearing carbon in the side chain of compound 5 was established in silico . The metabolites were evaluated for their antifungal activity and the bioactivity as agonist/antagonists of the liver X receptors (LXRs). Compound 4 presents antifungal activity and compounds 3 and 5 are the agonists of LXRs. Graphical Abstract: